Ceramic quality of the soils in the Chorotega region, Guanacaste, Santa Cruz y Nicoya, Costa Rica - Guadamuz, Diego A. (2023)
The study area is located between the towns of Santa Cruz and Nicoya, Guanacaste, it is a geographic area of 164 km2 with a dry to humid tropical climate, where igneous and sedimentary rocks are exposed on the surface. Our research it is a geological prospecting, evaluated and analyzed the clays from a mechanical, edaphological and ceramic perspective to determine the quality of the ceramic products generated using the soils in the study area. A total of 44 soil samples and 30 rock samples were collected from locations near the floodplain. The results obtained show that altered basalts bearing secondary aluminosilicate minerals and silica-rich sandstones are the main precursor rocks for clays used in the manufacture of ceramics by potters from Chorotega region. It is also verified that the soils of the study area belong to the vertisoils and alfisoils taxonomy, which can generate good quality ceramic pieces, since they are ballclay and fireclay type clays (Nelson, 1960). They show porosities between 51 % and 61 %, plasticity indexes raging from 14 to 29, densities greater than 1,7 g/cm3, a content of fines greater than 59,9 %, and when cooked, they have less than 11 % shrinkage and less than 30 % moisture loss. Therefore, the study concludes that the soils have the appropriate ceramic properties to be able to produce pieces with few ceramic defects, resistant and without problems either for their slip or for the final details and decorations.